2020
DOI: 10.1002/ca.23555
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the clavicular part of the deltoid muscle by the lateral pectoral nerve

Abstract: Introduction: The innervation pattern of the clavicular head of the deltoid muscle and its corresponding topography was investigated via cadaveric dissection in the present study, focusing on the lateral pectoral nerve. Materials and methods: Fifty-eight upper extremities were dissected and the nerve supplies to the deltoid muscle and the variability of the lateral pectoral and axillary nerves, including their topographical patterns, were noted. Results: The clavicular portion of the deltoid muscle received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Traditionally, nonsurgical methods have been recognized as the initial treatment modality for most clavicle fractures. However, recent studies have shown that surgical intervention may be more beneficial to patients [ 12 , 32 ]. Recent developments in regional anesthesia have led to a renewed interest in analgesia with a cervical plexus blockade for clavicle fracture surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, nonsurgical methods have been recognized as the initial treatment modality for most clavicle fractures. However, recent studies have shown that surgical intervention may be more beneficial to patients [ 12 , 32 ]. Recent developments in regional anesthesia have led to a renewed interest in analgesia with a cervical plexus blockade for clavicle fracture surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral nerves innervating the clavicle include branches of the axillary nerve, suprascapular nerve, and lateral thoracic nerve (C5, 6, and 7) [ 5 , 12 ]; the supraclavicular nerve (C3 and 4) [ 27 ]; branches of C2 to 3 [ 8 ]; the medial and lateral thoracic nerves (C8 to T1) [ 17 ]; and the subclavian nerve (C5 and 6). Theoretically, patients undergoing plate fixation for a clavicle fracture feel pain or discomfort unless all the associated nerves (C2 to T1) are blocked.…”
Section: Introductionmentioning
confidence: 99%